Toluene adsorption from waste air stream using activated carbon impregnated with manganese and magnesium metal oxides - F Rezaei; G Moussavi; A.R Riyahi Bakhtiari; Y Yamini (سلامت و محیط, 2016)
Background and Objectives: Adsorption is one of the most common methods for VOCs elimination from waste air stream. The study on the application of a selective and cheap adsorbent with high efficiency in VOCs removal is important from economic aspects. In this study, the potential of MnO/GAC and MgO/GAC composites was investigated for toluene adsorption from air stream at  lab scale.